Becoming visible with limited resources: Non-profit journalists’ perspectives on search engine optimization - Sebastian Schultheiß; Dirk Lewandowski (PLoS ONE, 2025)
This study examines the perspectives of non-profit online magazines regarding their online presence and the role that search engine optimization (SEO) plays in enhancing their visibility. We conducted semi-structured interviews with representatives from seven non-profit online magazines in Germany. Our findings indicate that visibility on the web is crucial for non-profits, even though they are not typically competing directly with commercial organizations. Non-profits seek visibility to achieve societal goals, such as educating their readership about fake news or promoting minority perspectives on political issues. Unlike for-profit organizations, economic factors are not their primary motivation. To reach their full potential audience, SEO is viewed as an important tool that all the surveyed magazines employ. However, due to limited resources, they cannot dedicate substantial effort to SEO and must treat it as a secondary task. The results of this study raise questions about how quality journalism from both for-profit and non-profit sources can reach the public in a balanced manner, as well as the responsibility search engine providers have in this context.